Legal Review of the Problems of Registering Creations as Written Documents of Copyright Ownership at the DJKI, Ministry of Law in Indonesia - Putri Rahmawati; Anis Mashdurohatun (Jurnal Hukum Khaira Ummah, 2025)
Abstract. This study examines in depth the mechanism of registering works as written documents of copyright ownership in Indonesia, as well as the accompanying problems, focusing on the dualism between the principle of automatic and declarative copyright protection as stipulated in Law No. 28 of 2014 concerning Copyright, and the existence of a registration mechanism organized by DJKI. The background of this research problem is driven by the importance of intellectual property rights as a manifestation of human intellectual abilities that are protected by law, abolished in the theory of natural rights and utilitarianism, as well as its constitutionality in Article 28D paragraph (1) of the 1945 Constitution of the Republic of Indonesia. Although copyrights appear automatically, the registration of works has a crucial function as an initial proof of ownership, which is later strengthened by the development of the E-Copyright system. However, this bold ease of access opens up the potential risk of data manipulation and overlapping claims, exacerbated by digital literacy challenges among creators. The purpose of this study is to analyze the effectiveness of the creation registration system in providing definite, fair, and beneficial protection for creators, as well as to identify the juridical and non-juridical content of this dynamic, including its relevance to the case of "Geprek Bensu" which illustrates the problem of ownership of rights and administrative compliance. This study uses normative juridical legal methods with a descriptive-analytical approach. The normative approach was chosen to analyze the legal principles written in Law No. 28 of 2014 concerning Copyright, as well as the relevant Civil Code and Trademark Law, in order to understand the declarative principles, the function of registering works, and the problems that arise. The research specification uses  a case approach to examine the case of "Geprek Bensu" as a concrete illustration,  a statute approach to meet compliance with applicable laws, and a contextual approach (conceptual approach). The results of the discussion concluded that the registration mechanism in Indonesia adheres to the principles of automatic and declarative protection, but Registration serves as a crucial initial proof of ownership, with the E-Copyright system increasing efficiency and accessibility but also opening up the risk of manipulation and overlapping claims. The main problem lies in the dualism between automatic protection and logging, which is compounded by the potential for double registration and juridical defects due to the ease of bold access. The case of "Geprek Bensu" is a clear reflection of this problem, where the court upheld  the principle of first to file for trademarks, but the DJKI's subsequent action to recommend the removal of recognized trademarks raises serious questions about the rule of law and administrative compliance. The analysis of the theory of the state of law and legal protection emphasizes the need for consistent law enforcement, equal treatment, and improvement of the administrative process of intellectual property rights registration in order to ensure certainty, fairness, and effective protection for all creators and rights holders.